"Nothing About Us, Without Us": Empowering the Youth Athlete Voice in #SafeSport - Mountjoy, M.; Vertommen, T.; Greinig, S.; Burrows, K.; Tercier, S. (Clinical Journal of Sport Medicine, 2022)
Safe sport is defined by the International Olympic Committee (IOC) as "an athletic environment that is respectful, equitable, and free from all forms of nonaccidental violence (harassment and abuse) to athletes" Although there are many physical and psychosocial benefits of sport participation, harassment and abuse experienced during sport can have a negative impact on athlete health and well-being. The IOC consensus statement authors identify 5 forms of harassment and abuse in sport: psychological abuse, physical abuse, neglect, sexual abuse, and sexual harassment. Much has been accomplished in the field with the introduction of the Safeguarding Framework at the 2016 Olympic Games, and the launch of the IOC Toolkit to assist International Federations and National Olympic Committees with the creation and implementation of athlete safeguarding policies and procedures. There has also been an increase in scientific publications illuminating the prevalence of harassment and abuse. In addition, knowledge translation initiatives have been developed to inform athletes of their right to safe sport that were implemented at the Youth Olympic Games (YOG) in both the Summer 2018 and the Winter 2020 editions.